Strange Affinities : The Gender and Sexual Politics of Comparative Racialization - Ferguson, Roderick A.; Hong, Grace Kyungwon (Book collections on Project MUSE., 2011)
Collection of essays that use queer studies and feminism as a lens for examining the relationships between racialized communities.